The Bending Vibrations of an Anisotropic Free Circular Plate of Regular Symmetry - Klimasek, A.; Pilski, A.O.; Zabawa, J. (Engineering Transactions, 1983)
The elasticity moduli determination method of the regular symmetry ingle crystals by bending vibrations ęxcitation in circular plate samples with the middle planes perpendicular to the crystallographic [100] and [110] directions is given in the work. The adaptation of the method for any other pair of directions presents no difficulties. Resonance frequencies of the free edge circular anisotropic plate were determined, too. In order to solve Eqs. (3.1) and (3.3), the consecutive approximation method was used. The method seemed to be the most simple and proper in this case. It enabled to give evident dependence between the resonance frequency of the sample and the elasticity moduli and the Poisson constant. Measurements were taken for Si and Ge single crystals.